2020
DOI: 10.1016/j.meegid.2019.104126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mycobacterium tuberculosis genetic lineages circulating in Riga and Riga region, Latvia, isolated between 2008 and 2012

Abstract: Although the number of new tuberculosis (TB) cases registered per year has decreased by 3-fold between 2001 and 2017 in Latvia, the TB incidence and rates of multidrug resistant TB in this Baltic country remain substantially higher than in most other European countries. Molecular typing methods of Mycobacterium tuberculosis (MTB) play an important role both in clinical studies of the disease and the epidemiological investigations, allowing to describe and characterize the pathogen's population structure and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
(23 reference statements)
3
17
0
Order By: Relevance
“…After evaluating the potential documents, 41 eligible studies were identified [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ]. These studies were conducted between 2006–2020 in Europe, Latin America, Asia, and Africa.…”
mentioning
confidence: 99%
“…After evaluating the potential documents, 41 eligible studies were identified [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ]. These studies were conducted between 2006–2020 in Europe, Latin America, Asia, and Africa.…”
mentioning
confidence: 99%
“…Prevalence of the main M. tuberculosis genotypes in Estonia (this study), Poland (SITVIT2), Latvia (Pole et al., 2020), Murmansk, Russia (Mäkinen et al, 2011), Belarus, reanalysed (Zalutskaya et al, 2013), Sweden (Jonsson et al, 2014), Pskov (Mokrousov, Vyazovaya, et al, 2012), Kaliningrad (Vyazovaya et al, 2017), Finland (Smit et al., 2013) and Karelia (Mokrousov et al, 2015). Free map: http://www.amaps.com/mapstoprint/OUTLINE%20MAPS/free_map_of_world.htm…”
Section: Resultsmentioning
confidence: 67%
“…For example, LAM-RUS is mainly drug-susceptible in Albania, similar to other M. tuberculosis genotypes in that country (Tafaj et al, 2020). In Latvia, not only Beijing SIT1 but also LAM SIT42 were overrepresented among MDR strains (Pole et al, 2020).…”
Section: Changes In Drug Resistancementioning
confidence: 85%
See 2 more Smart Citations